2017
DOI: 10.1016/j.diabres.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance correlates with maculopathy and severity of retinopathy in young adults with Type 1 Diabetes Mellitus

Abstract: IR correlates with more severe retinopathy in young adults with Type 1DM. This is the first description of a correlation between IR and maculopathy in Type 1DM, warranting further evaluation. Prospective studies examining whether reducing IR can improve microvascular complications are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The level of IL-6 has been reported linearly associated with an increase of neovascularization activity in PDR 244 . Moreover, a cross-sectional study confirmed a relationship between IR and severity of retinopathy in diabetic patients 245 . Together, these results imply that IL-6 might be critical in mediating insulin-induced vascular remodelling.…”
Section: Discussionmentioning
confidence: 69%
“…The level of IL-6 has been reported linearly associated with an increase of neovascularization activity in PDR 244 . Moreover, a cross-sectional study confirmed a relationship between IR and severity of retinopathy in diabetic patients 245 . Together, these results imply that IL-6 might be critical in mediating insulin-induced vascular remodelling.…”
Section: Discussionmentioning
confidence: 69%
“…22 Patients with DR have two to four times the risk of developing cardiovascular events as those without DR. 23 PStudies have revealed that IR is correlated with severe DR in type 1 diabetes, especially in PDR. 24,25 HOMA-IR is calculated based on FPG and insulin, 16 mainly reflecting the state of glucose metabolism, while the TyG index is calculated on the basis of FPG and TGs, 10 representing the joint effects of glucose and lipids.…”
Section: Dovepressmentioning
confidence: 99%
“…Moreover, Rowe et al confirmed a relationship between IR and more severe DR in patients with type 1 DM. 33 It was also demonstrated by Duţă et al 34 that eGDR was the most important factor of proliferative DR.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, Rowe et al confirmed a relationship between IR and more severe DR in patients with type 1 DM. 33 It was also demonstrated by Duţă et al 34 that eGDR was the most important factor of proliferative DR. The use of eGDR has been recently advocated as a useful way to assess IR.Several studies have demonstrated that a lower eGDR is associated with higher IR.…”
mentioning
confidence: 84%